One dimensional state space approach to thermoelastic interactions without energy dissipation - Mukhopadhyay S. (My University, 2025)
The present work is concerned with the formulation of state space approach to the problems of thermoelastic interactions without energy dissipation in a thermoelastic medium. The formulation together with the Laplace transform procedure is applied for the problem of a half space whose boundary is subjected to (i) ramp type increase in temperature and zero stress and (ii) ramp type increase in load and zero temperature change. Closed form solutions are obtained for both the problems for the distributions of the displacement, temperature and stress of the medium. The results are compared with the earlier findings. Numerical works are also performed for a suitable material with the aim of illustrating the results.